Northeast Tibetan Crustal Structure from INDEPTH IV Controlled- Source Seismic Data - Karplus, Marianne; Klemperer, Simon; Wenjin, Zhao; Zhenhan, Wu; Danian, Shi; Heping, Su; Brown, Larry; Chen, Chen; Mechie, Jim; Kind, Rainer; et al. (Himalayan Journal of Sciences, 2008)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–> <!–[if gte mso 10]> <![endif]–> DOI = 10.3126/hjs.v5i7.1274 Himalayan Journal of Sciences Vol.5(7) (Special Issue) 2008 p.76-77